Agata and the Storm - Agata e la tempesta - Silvio Soldini (2004)
When Agata, popular bookshop proprietor and dispenser of sunny wisdom in the form of books, is suddenly wooed by a man almost half her age, her electricity hits high-voltage. It even sends light bulbs, computers and other electrical appliances bursting in her wake.Agata's brother Gustavo - a rather self-satisfied, pampered successful architect - is not sheltered from the brewing storm of life either. The shock when he discovers he is in fact an adopted son, "bought" by his parents as an infant, shakes the very foundations of his certitudes. The winds of change soon rage at gale force as he is forced to admit his true feelings about his joyless marriage and mediocre life. An incorrigible skirt-chaser and traveling salesman appropriately named Romeo, as garish as his clothing lines, turns out to be Gustavo's unlikely real brother. The chorus of this ensemble comedy reaches impossible heights of laughter and tenderness in the adventures of the bizarre triangle.
Keywords: Comedy, Romance